Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1245/s10434-010-1000-9
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Role for MRI in the Preoperative Assessment of Patients with DCIS?

Abstract: MRI does not accurately predict extent of disease in patients with extensive DCIS. In patients with MRI tumor size < or = 2 cm, MRI may assist in surgical planning. MRI results in patients with DCIS should be interpreted with caution; decision for mastectomy should not be made on MRI findings alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…Nine studies were eligible for the meta‐analysis; seven of these were studies that compared cohorts defined by whether or not MRI was performed, and two were RCTs of preoperative MRI. Four studies included patients with both DCIS and invasive breast cancer, whereas five included patients with DCIS only. Four studies included patients undergoing BCS as primary surgery, whereas five evaluated preoperative MRI in patients scheduled for either mastectomy or breast conservation as initial surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were eligible for the meta‐analysis; seven of these were studies that compared cohorts defined by whether or not MRI was performed, and two were RCTs of preoperative MRI. Four studies included patients with both DCIS and invasive breast cancer, whereas five included patients with DCIS only. Four studies included patients undergoing BCS as primary surgery, whereas five evaluated preoperative MRI in patients scheduled for either mastectomy or breast conservation as initial surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that examine patients with DCIS alone have not shown a decrease in positive margins or the need for re-excision, and some show unnecessary increases in mastectomy rates. 1821 In addition, two large, randomized trials have evaluated the addition of preoperative breast MRI in women undergoing BCS for breast carcinoma; one found no difference in reoperation rates (19 vs. 19 %, p = 0.77), whereas the other showed a paradoxical increased rate of re-excision among women randomized to MRI. 22,23 Of note, just over 70 % of the re-excisions in the latter study were for DCIS, suggesting that MRI was relatively insensitive to extent of DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, Kuhl et al 22 investigated pure DCIS and achieved a much higher sensitivity to detecting DCIS by MRI (92%, compared to a mammogram 56%, P < 0.0001) and which was particularly sensitive to high grade DCIS. Age, menopausal status, personal or family history of breast cancer or of benign breast disease and breast density of women with MRIonly diagnosed DCIS did not differ significantly from those of women with mammography-diagnosed DCIS.…”
Section: Detection Of Additional Diseasementioning
confidence: 99%